Analisis Kinerja Tender dengan Sistem Penilaian Kualifikasi â€œNilai Pengalaman Tertinggiâ€ pada Perusahaan Konstruksi - Lisa, Ulfa Sama; Azhar, Moh.; Sembiring, Kristina; Maharani, Sri (Universitas Batanghari Jambi, 2024)
Bidding activities in a job are carried out through a tender offer to select up to the process of appointing which company is appropriate in carrying out a work package. The method for determining the winner of the tender can be done by knockout method, value or cost assessment. Bidding that is usually made by companies can have several problems, while the main thing that often arises is that bids are made too high in the hope that bidders can get a large profit, or vice versa they cannot offer prices that are too low due to the hope of getting a project opportunity. the greater it is. Companies that procure both goods and services are carried out efficiently, effectively, transparently, openly, competitively, fairly and accountably. Based on BPS data by DataIndonesia.ID, there are 131,414 companies in Indonesia in 2021. This number has increased by 1.76% compared to the previous year of 129,137 companies. The large number of construction companies has the impact of increasing competition between companies in winning an auction/tender. The purpose of this study was to analyze the Tender Performance With the Highest Experience Value Qualification Rating System in Construction Companies. The method used in this research is descriptive method with purposive sampling technique. The sample of this research is 88 companies located in Jabodetabek. The results showed that there was an effect of the highest experience value on winning tenders in construction companies in Jakarta with a p value <0.005. The conclusion in this study is that the highest experience value rating system affects the evaluation of tender acceptance qualifications in construction companies.